2006
DOI: 10.5713/ajas.2006.739
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Proteolysis of Breast and Leg Muscles from Taiwan Colored Chickens and Silkie Bantams

Abstract: Postmortem proteolysis of breast (BM) and leg (LM) muscles from Taiwan colored chickens (TCC) and silkie bantams (SB) at 5°C were compared. Myofibrils were prepared from BM and LM samples that were randomly taken from the carcasses of SB and TCC after 0, 1, 3, 7 and 14 days of storage at 5°C. pH of samples was determined, and degradation of myofibrillar proteins was analyzed by the SDS-PAGE and western blots. The results showed that pH was lower in BM than in LM samples from both avian strains. Appearance of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(37 reference statements)
4
0
0
Order By: Relevance
“…These results were consistent with the findings of Lee et al ,23 who showed that the ultimate pH in chicken muscle was reached by 6 h post mortem. Figure 1 also shows that the pH was significantly ( P < 0.05) lower in the BM than in the LM samples after 24 h postmortem storage at 5 °C, consistent with our previous report 24. This difference might be attributed to the higher content25 and to the faster utilization23 of muscle glycogen in chicken breast muscle.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results were consistent with the findings of Lee et al ,23 who showed that the ultimate pH in chicken muscle was reached by 6 h post mortem. Figure 1 also shows that the pH was significantly ( P < 0.05) lower in the BM than in the LM samples after 24 h postmortem storage at 5 °C, consistent with our previous report 24. This difference might be attributed to the higher content25 and to the faster utilization23 of muscle glycogen in chicken breast muscle.…”
Section: Resultssupporting
confidence: 89%
“…2) decreased more rapidly than LM desmin (Fig. 2), confirming previous studies 24. In BM samples, most of the desmin remained intact in 3 h postmortem samples, which contained ∼85% of the desmin present in BM sampled at death.…”
Section: Resultssupporting
confidence: 88%
“…Figure 1 shows that the pH was significantly lower ( P < 0.05) in BM than in LM during 14 days postmortem storage at 5 °C, similar to our previous findings in chicken muscle 17, 28. The average at‐death pH was 6.25 ± 0.13 in BM samples and decreased significantly to 5.96 ± 0.11 ( P < 0.05) by 1 day post mortem (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Western blots labeled with a desmin monoclonal antibody indicate that BM desmin decreased more rapidly than LM desmin (Fig. 2), consistent with the changes in postmortem chicken muscle 17, 28. In BM samples, the abundance of desmin in 1‐day postmortem samples decreased to ∼57% of the abundance in the at‐death samples.…”
Section: Resultssupporting
confidence: 71%